Off the charts!

Calculus Level 5

0 1 ( ln x ) 3 x 2 1 d x \large \int_0^1 \dfrac {(\ln x)^3}{x^2- 1} \, dx

If the integral above is equal to π A 2 B \dfrac {\pi^A}{2^B} , where A A and B B are integers, find the value of A + B A+B .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ishan Tarunesh
Dec 4, 2015

Hmm.. Nice

Mayank Bhardwaj - 5 years, 6 months ago

Sir, would you happen to know any good links from which I could learn more on solving multivariable recurrences?

First Last - 5 years ago
Hassan Abdulla
Jun 7, 2018

let I = 0 1 ( ln x ) 3 x 2 1 d x put x = e u I = 0 u 3 e u d u 1 e 2 u 1 1 e 2 u = k = 0 e 2 k x sum geometric series I = 0 k = 0 u 3 e u e 2 k u d u = k = 0 0 u 3 e u ( 2 k + 1 ) d u put u = t ( 2 k + 1 ) I = k = 0 1 ( 2 k + 1 ) 4 0 t 3 e t d u = k = 0 Γ ( 4 ) ( 2 k + 1 ) 4 = 3 ! k = 0 ( 1 ( 2 k + 1 ) 4 + 1 ( 2 k + 2 ) 4 1 ( 2 k + 2 ) 4 ) I = 6 ( k = 1 1 k 4 k = 1 1 16 k 4 ) = 6 ζ ( 4 ) ( 1 1 16 ) = 6 π 4 90 15 16 = π 4 16 = π 4 2 4 note that ζ ( 4 ) = π 4 90 \begin{matrix} \text{let }I=\int_0^1 {\dfrac {(\ln x)^3}{x^2- 1} dx} & & & \color{#D61F06} \text{put }x=e^{-u} \end{matrix} \\\Rightarrow \begin{matrix} I=\int_0^{\infty} {\dfrac {u^3e^{-u}du}{1-e^{-2u}}} & & & \color{#D61F06} \dfrac {1}{1-e^{-2u}}=\displaystyle\sum_{k=0}^\infty{e^{-2kx}} & \color{#D61F06} \text{sum geometric series} \end{matrix} \\\Rightarrow \begin{matrix} I=\int_0^{\infty} {\displaystyle\sum_{k=0}^\infty{u^3e^{-u}e^{-2ku}}du}= \displaystyle\sum_{k=0}^\infty{\int_0^{\infty}{u^3e^{-u(2k+1)}}du} & & & \color{#D61F06} \text{put }u=\frac{t}{(2k+1)} \end{matrix} \\\Rightarrow I=\displaystyle\sum_{k=0}^\infty{\frac{1}{(2k+1)^4}\int_0^{\infty}{t^3e^{-t}}du}=\displaystyle\sum_{k=0}^\infty{\frac{\Gamma(4)}{(2k+1)^4}}=3!\displaystyle\sum_{k=0}^\infty{\left ( \frac{1}{(2k+1)^4}+\frac{1}{(2k+2)^4}-\frac{1}{(2k+2)^4} \right )} \\\Rightarrow I=6\left ( \displaystyle\sum_{k=1}^\infty{\frac{1}{k^4}} -\displaystyle\sum_{k=1}^\infty{\frac{1}{16k^4}}\right)=6\cdot\zeta(4)\cdot(1-\frac{1}{16})=6\cdot\frac{\pi^4}{90}\cdot\frac{15}{16}=\frac{\pi^4}{16}=\frac{\pi^4}{2^4} \\ \text{note that }\zeta(4)=\frac{\pi^4}{90}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...